The Role of Public Relations in Maintaining the Existence of the General Hospital Sayang Bunda Makassar - Andi Khairul Musyawir; Indrayanto Indrayanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background : The problem found at the Sayang Bunda Makassar General Hospital was a decrease in patients after the end of COVID-19 in 2023, there were visit data of 147 patients in January – July. Objective : The purpose of this study is to determine the role of Public Relations in increasing the existence of the hospital. Method : This type of research used qualitative research methods. Methods collected documentation data and in-depth interviews to Result : The research results obtained at the general hospital unfortunately have not been fulfilled in terms of social activities which were only held in 2020, as for the results of observations of social activities and published on social media, this provides satisfaction that the service at the general hospital unfortunately has not collaborated with BPJS insurance, as for communication through media, it has not been fulfilled so that the internet is widely used, social media such as Instagram, as well as the educational dimension when carrying out activities. such as handling mass circumcisions or providing direct health services. Suggestion : The hospital needs to improve marketing management by digitalizing marketing, promoting health through electronic media as well as re-organizing social activities, improving facilities and infrastructure as well as access to payment via card (JKN-KIS) at Sayang Bunda General Hospital.